Premature Mortality from Type 2 Diabetes Mellitus Attributable to Household Air Pollution from Solid Fuels in Eastern Sub-Saharan Africa, 1990 to 2023 - Mihretu Tagesse Sergindo; Begetayinoral Kussia Lahole; Abraham Lomboro Dimore; Melese Chego Cheme; Sina Temesgen Tolera; Hirut Teame; Embay Amare Alemseged; Medhin Mehari; Yonas Angaw; Hailu Lemma; Lechisa Asefa; Degefa Dhengesu Hero; et al. (Environmental Health Insights, 2026)
Background Type 2 diabetes mellitus is a growing public health crisis in Sub-Saharan Africa, where household air pollution from solid fuel use is a common contributor. This study estimated the premature mortality burden from type 2 diabetes mellitus attributable to household air pollution in the Eastern Sub-Saharan Africa region from 1990 to 2023. Methods A systematic analysis was conducted using data from the Global Burden of Diseases 2023 study for the Eastern Sub-Saharan countries. The Comparative Risk Assessment framework was used to estimate years of life lost (YLLs) by sex, age, and country. The percentage change between 1990 and 2023 was quantified to estimate the net change. Results There were an estimated 276,327 YLLs (95% UI: 165093, 422324) from Type 2 diabetes attributable to household air pollution from solid fuels in the Eastern Sub-Saharan-Africa region in 2023. The equivalent age-standardized rate was estimated to be 134 YLLs per 100,000 population (95% UI: 80, 206). Among adults aged 20 to 54 years old, there were an estimated 57 YLLs 100,000 (95% UI: 35, 88), and above 55 years old it was estimated 562 YLLs per 100,000 (95% UI: 334,862). There was no significant variation in the rate by sex and location throughout the region. The rate showed no improvement between 1990 and 2023 and increased with age. Conclusion Household air pollution from solid fuels caused a significant premature mortality related to type 2 diabetes mellitus in the Eastern Sub-Saharan Africa region, with a stagnant impact from 1990 to 2023 and a disproportionate impact on older adults. Thus, there is a critical need to integrate clean energy access with type 2 diabetes mellitus prevention and control strategies to ensure health equity in the region.